2021
DOI: 10.1063/5.0036284
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photons produced from a plasma-cathode electron beam for radiation biology applications

Abstract: A compact low-energy and high-intensity x-ray source for radiation biology applications is presented. A laser-induced plasma moves inside a 30 kV diode and produces a beam of 1014 electrons at the anode location. An aluminum foil converts a part of the energy of these electrons into x-ray photons, which are characterized using filtered imaging plates. The dose that would be deposited by these x-ray photons in C. elegans larvae is calculated from Geant4 simulations. It can be set to a value ranging between 10 μ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The experiment is even more complicated as a strong flash of X-ray photons will be emitted during the slowing down of the incident electrons in the anode over a duration of a few tens of ns. In a previous study [29], we have shown that the total energy of the photons of this flash was of the order of 10 9 to 10 10 keV in the backside of a 15 µm thick aluminum anode. Such an amount of energy cannot totally relax in a scintillator or semiconductor detector [30] over a few tens of µs, i.e.…”
Section: A γ-Ray Photonsmentioning
confidence: 70%
“…The experiment is even more complicated as a strong flash of X-ray photons will be emitted during the slowing down of the incident electrons in the anode over a duration of a few tens of ns. In a previous study [29], we have shown that the total energy of the photons of this flash was of the order of 10 9 to 10 10 keV in the backside of a 15 µm thick aluminum anode. Such an amount of energy cannot totally relax in a scintillator or semiconductor detector [30] over a few tens of µs, i.e.…”
Section: A γ-Ray Photonsmentioning
confidence: 70%